Comics on Instagram: the formation of the responsive reader - Souza, Daize Miranda Oliveira; Souza, Bruno Henrique Castro de; Chisté, Priscila de Souza (The ESPecialist, 2025)
The current technological context points to a change in social areas, including education. This article aims to demonstrate how teaching and learning Portuguese can be more meaningful and attractive to students if combined with technology. It discusses how the comic genre, associated with Instagram support, through a specific account is used to stimulate and enhance students’ responsiveness. Therefore, the proposal of this article unites the linguistic and technological skills of students and promotes dialogue between the informality of social media andcomics. The elaboration of this article was based on Bakhtin’s theories on genres and responsive reading; on Pinheiro’s thoughts on media genres; as well as on Marcuschi’s on textual support.